2013
DOI: 10.26719/2013.19.supp3.s194
|View full text |Cite
|
Sign up to set email alerts
|

Nelaton catheter assisted versus standard nasogastric tube insertion: a randomized, clinical trial

Abstract: It is sometimes difficult to insert a nasogastric tube in an anaesthetized patient. We evaluated the benefit of reinforcing the distal portion of the nasogastric tube with a Nelaton catheter: 8 and 10 French Nelaton catheters were inserted into 16 and 18 French nasogastric tubes respectively through the first proximal holes of tubes up to their tips. The patients anaesthetized were randomly allocated into either the control or the Nelaton groups, and nasogastric tube was inserted as deeply as the catheter leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The main focus of these kinds of techniques is simplicity and decreasing complications to a minimum. Ghaemi et al [32] compared nelaton catheter assisted versus standard NGT insertion and showed that nelaton group had a high success rate and shorter duration for insertion compared to the control group. Najafi [22] introduced a new method, namely the "SORT manoeuvre" for NGT placement in patients who cannot swallow.…”
Section: Insertion Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main focus of these kinds of techniques is simplicity and decreasing complications to a minimum. Ghaemi et al [32] compared nelaton catheter assisted versus standard NGT insertion and showed that nelaton group had a high success rate and shorter duration for insertion compared to the control group. Najafi [22] introduced a new method, namely the "SORT manoeuvre" for NGT placement in patients who cannot swallow.…”
Section: Insertion Techniquesmentioning
confidence: 99%
“…Ultrasonography [30] Ph indicator [36,37] Stridor [47] Pulmonary aspiration [50] Sort maneuver [22,23] Airway scope [31] Electromagnetic device [38] Pneumothorax [51] Nelaton [32] Chemical assessment of aspirates (Ph, trypsin, bilirubin, CO 2 and pepsin) [39,40] Perforation of lamina cribrosa [52] Tube length End tidal CO 2 monitoring [41] Retropharyngeal abcess [47] Fluroscopy [42] Stricture formation Endoscopy [42] Aortoesophageal fistula [52] Manometer [43,44] Nasogastric tube syndrome [53,54] (TEE) probe insertion (See video at: http://atlasofscience. org/nasogastric-tube-insertion-the-simple-yet-impossible/ accessed 11 Nov 2016).…”
Section: By Equipment Minor Majormentioning
confidence: 99%
“…Zhao et al [ 13 ] compared the conventional NGT insertion technique with NGT placement in the right lateral decubitus position and found a statistically significant difference in the rates of successful insertion in the first attempt, overall success, insertion time, and complications (gag reflex, cough, and mucosal bleeding) with the right lateral decubitus position. Ghaemi et al [ 25 ] compared Nelaton catheter-assisted NGT placement with the conventional technique and showed a higher rate of successful insertion with relatively shorter insertion duration in the Nelaton group. Wan Ibadullah et al [ 21 ] documented a higher, although non-significant, success rate of insertion for the GlideScope compared to the Macintosh laryngoscope.…”
Section: Resultsmentioning
confidence: 99%